2004
DOI: 10.1614/wt-03-106r
|View full text |Cite
|
Sign up to set email alerts
|

Use of Quinclorac for Large Crabgrass (Digitaria sanguinalis) Control in Newly Summer-Seeded Creeping Bentgrass (Agrostis stolonifera)

Abstract: Field trials were conducted in 2000 and 2001 in New Jersey to evaluate quinclorac and siduron for large crabgrass control in summer-seeded creeping bentgrass (‘L-93’). Bentgrass was surface seeded on June 30 and June 26 in 2000 and 2001, respectively. Treatments consisted of preemergence (PRE) applications of siduron at 3.4, 5.0, and 6.7 kg ai/ha and PRE and postemergence (POST) applications of quinclorac at 0.4, 0.6, 0.8, and 1.7 kg ai/ha. POST applications were timed to a crabgrass growth stage of three leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 7 publications
1
21
0
Order By: Relevance
“…At 4 WAS, mesotrione applied at 0 and 2 WAS reduced ground cover 19 and 28% from the nontreated check, respectively. Similar reductions in creeping bentgrass density have been reported with quinclorac during establishment (Hart et al 2004). Despite significant injury from mesotrione, creeping bentgrass ground cover was similar or greater than the nontreated control from 8 to 20 WAS.…”
Section: Resultssupporting
confidence: 79%
“…At 4 WAS, mesotrione applied at 0 and 2 WAS reduced ground cover 19 and 28% from the nontreated check, respectively. Similar reductions in creeping bentgrass density have been reported with quinclorac during establishment (Hart et al 2004). Despite significant injury from mesotrione, creeping bentgrass ground cover was similar or greater than the nontreated control from 8 to 20 WAS.…”
Section: Resultssupporting
confidence: 79%
“…However, siduron applied in the June seeding of 2011 as well as July seedings of both years resulted in 20 to 82% crabgrass cover, compared to ≤4% crabgrass cover in the mesotrione‐ or quinclorac‐treated plots (Table 2). Hart et al (13) showed similar results on newly‐seeded creeping bentgrass where sequential applications of quinclorac consistently provided effective weed control and turf safety.…”
Section: Effects Of Sequential Herbicide Applications On Tall Fescue mentioning
confidence: 84%
“…Quinclorac is a quinolinecarboxylic acid herbicide that causes cyanide accumulation in susceptible grasses, leading to phytotoxicity, root and shoot growth inhibition, and eventual necrosis (Ferrell et al, 2003;Grossman, 1998;Koo et al, 1994;Senseman, 2007). Quinclorac has been shown to provide effective POST control of smooth crabgrass in various cool-and warm-season turfgrasses (Chism and Bingham, 1991;Dernoeden et al, 2003;Enache and Ilnicki, 1991;Hart et al, 2004;Johnson, 1994aJohnson, , 1994bJohnson, , 1995Johnson, , 1996Reicher et al, 1999); however, turfgrass injury after treatment with quinclorac has been reported to vary considerably. For example, Johnson (1997) reported as high as 65% centipedegrass [Eremochloa ophiuroides (Munro) Hack] injury after treatment with quinclorac at 0.84 kgÁha -1 .…”
mentioning
confidence: 99%